Foreigners and Egyptians in the late Egyptian stories : linguistic, literary and historical perspectives - Biase-Dyson, Camilla Di. (Probleme der Ägyptologie, 2013)
In Foreigners and Egyptians in the Late Egyptian Stories Camilla Di Biase-Dyson applies systemic functional linguistics, literary theory and New Historicist approaches to four of the Late Egyptian Stories and shows how language was exploited to establish the narrative roles of literary protagonists. The analysis reveals the shifting power dynamics between the Doomed Prince and his foreign wife and the parody in the depiction of the Hyksos ruler Apophis and his Theban counterpart Seqenenre. It also sheds light on the weight of history in the sketch of the Rebel of Joppa and the general Djehuty and explains the interplay of social expectations in the encounters between the envoy Wenamun and the Levantine princes with whom he seeks to trade. \'Overall, Di Biase-Dyson's monograph is an original interdisciplinary examination of an exciting corpus of ancient literary texts.\' Nikolaos Lazaridis, Journal of Near Eastern Studies